Role of mechanical factors in applications of stimuli-responsive polymer gels – Status and prospects. (28th September 2016) - Goponenko, Alexander V.; Dzenis, Yuris A.
Abstract: Due to their unique characteristics such as multifold change of volume in response to minute change in the environment, resemblance of soft biological tissues, ability to operate in wet environments, and chemical tailorability, stimuli-responsive gels represent a versatile and very promising class of materials for sensors, muscle-type actuators, biomedical applications, and autonomous intelligent structures. Success of these materials in practical applications largely depends on their ability to fulfill application-specific mechanical requirements. This article provides an overview of recent application-driven development of covalent polymer gels with special emphasis on the relevant mechanical factors and properties. A short account of mechanisms of gel swelling and mechanical characteristics of importance to stimuli-responsive gels is presented. The review highlights major barriers for wider application of these materials and discusses latest advances and potential future directions toward overcoming these barriers, including interpenetrating networks, homogeneous networks, nanocomposites, and nanofilamentary gels. Graphical abstract: Highlights: Stimuli responsive gels are versatile, rapidly developing class of materials. Mechanical aspects of gels are important but have not been sufficiently studied. Low response rate and poor mechanical robustness remain critical issues for applications. New ways to enhance gel response speed and robustness need to be developed. Nanofilamentary materials that combine speed of nanogels with macroscopic size represent one possible solution.